Small intestinal bacterial overgrowth in patients with systemic sclerosis - Saara Rawn; Natalia Pitman; Karen Beattie; Ava Bazzaz; Maggie Larche (Indian Journal of Rheumatology)
Small intestinal bacterial overgrowth (SIBO) is common in patients with systemic sclerosis (SSc) yet often goes underrecognized in clinical practice. In patients with SSc, untreated SIBO may result in marked morbidity and possible mortality. The pathogenesis of SIBO is multifactorial and relates to immune dysregulation, vasculopathy, and dysmotility. This article reviews various diagnostic approaches and therapeutic options for SIBO. Treatment modalities mainly include prokinetics, probiotics, and antibiotics.